An interior penalty method for optimal control problems with state and input constraints of nonlinear systems. (5th September 2014) - Malisani, P.; Chaplais, F.; Petit, N.
Summary: This paper exposes a methodology to solve state and input constrained optimal control problems for nonlinear systems. In the presented 'interior penalty' approach, constraints are penalized in a way that guarantees the strict interiority of the approaching solutions. This property allows one to invoke simple (without constraints) stationarity conditions to characterize the unknowns. A constructive choice for the penalty functions is exhibited. The property of interiority is established, and practical guidelines for implementation are given. A numerical benchmark example is given for illustration. © 2014 The Authors. Optimal Control Applications and Methods published by John Wiley & Sons, Ltd.